UTILIZATION OF SWEET POTATO DODOL AS ADDITIONAL FOOD FOR ELEMENTARY SCHOOL WITH MALNUTRITION CHILDREN'S - Mustamir Kamaruddin; Yulia Rachmawati (GEMA KESEHATAN, 2022)
The successful development of a nation is influenced by quality human resources, namely human resources, which are physically demanding, mentally strong, in excellent health, and have a good level of achievement. The development and training of exceptional quality human resources start early when they are school-age. Based on the 2018 Riskesdas, the prevalence of wasting in Sorong City is 10.7%, which means it is above the national average majority. School-age children are in a period of transition from children to adults. There is mental, physical, and emotional growth that is quite fast at this time. Providing Supplemental Food for School Children is a program to restore the nutritional intake of students in elementary schools. Apart from improving nutrition, this program is also helpful for introducing children to healthy and nutritious food. The research was conducted in 2 elementary schools in Sorong City from July to November 2021. The study aimed to analyze the effect of giving purple sweet potato dodol on weight gain in malnourished children. Malnourished children were obtained through screening in 2 schools. The study used a quasi-experimental design using the Pretest-Posttest Control Group Design. The sample was 30 malnourished children who were divided into an experimental group and a control group. The sampling technique is accidental sampling. Data collection was carried out by measuring body weight using digital scales. The statistical test uses the independent sample t-test. The results showed that giving purple sweet potato dodol as much as 100 grams/day/child increased the weight of malnourished children. Purple sweet potato dodol of 100 gr/day/child is recommended as a supplementary food for malnourished children with consideration of its acceptability and good nutritional value. Socialization of functional food as a basic ingredient in increasing the weight of children with undernourished status must be encouraged.  Keywords: Dodol, Malnutrition, Purple Sweet Potato, Supplementary Food Weight